Multi-variable models of large International Prostate Symptom Score worsening at the end of therapy in prostate cancer radiotherapy. Issue 1 (January 2016) - Palorini, Federica; Rancati, Tiziana; Cozzarini, Cesare; Improta, Ilaria; Carillo, Viviana; Avuzzi, Barbara; Casanova Borca, Valeria; Botti, Andrea; Degli Esposti, Claudio; Franco, Pierfrancesco; Garibaldi, Elisabetta; Girelli, Giuseppe; et al.
Abstract: Purpose/objective: Prospectively assessing clinical/dosimetry factors affecting the acute worsening of urinary functionality after radiotherapy for prostate cancer. Material/methods: DUE01 population was considered, including patients treated with conventional or moderate hypo-fractionation (2.2–2.7 Gy/fr). Relevant clinical factors were collected, urinary symptoms were self-reported through the International Prostate Symptom Score (IPSS) before and at the end of radiotherapy; while absolute weekly dose–surface histograms (DSHw ) were chosen as dosimetry descriptors. An IPSS increase of at least 10 and 15 points (ΔIPSS ⩾ 10 and ΔIPSS ⩾ 15) were chosen as endpoints. Patients with baseline IPSS > 20 were excluded. Relevant factors were chosen through a bootstrap-based in silico methodology. Results: Complete information was available for 380 patients: 77/380 (20%) and 28/380 (7%) with ΔIPSS ⩾ 10 and ΔIPSS ⩾ 15, respectively. Neoadjuvant hormone was protective (OR = 0.49 and 0.69). DSHw at 8.5 Gy/week and 12 Gy/week were risk factors, with additional risk for patients who use cardiovascular drugs and anti-hypercholesterolemia drugs. In the hypo-fractionated subgroup ( n = 209) the role of cardiovascular drugs (OR = 2.16) for ΔIPSS ⩾ 10 and anti-hypercholesterolemia drugs (OR = 2.80) for ΔIPSS ⩾ 15, together with DSHw (10 Gy/week and 12.5 Gy/week, respectively), was confirmed. Conclusion: Current study shows a dose–surface/volume effect for acute large worsening of urinary functionality; several clinical variables largely impact the risk and especially all the factors related with vascular diseases.